The Discourse Movement Analysis of Hashtags Supporting the Legalization of Same-Sex Marriage - Putri, Aprilia Kartika; Fitriah, Siti; Triandana, Anggi; Amri, Ulil; Putra, Yoga Mestika (English Department, Faculty of Humanities, Andalas University, 2025)
The legalization of same-sex marriage in the United States on June 26, 2015 inflicted rooms for debates. The contra side included the conservative Christian groups. Meanwhile, the Pro side celebrated the ruling by waving rainbow flags in front of the Supreme Court building and using #LoveWins and #Pride hashtags in their social media, such as Twitter and Instagram. This paper describes the analysis of these discourses movements by using Sawirman’s BREAK theory (2014; 2016). #LoveWins was considered as the primary discourse while #Pride as the secondary because of their political power. Both hashtags were used to show the joy and support for the gay community. As the time goes on, the secondary disourse is used more frequent than the primary, which is only used in the moments of equality of right between the gay and straight community.